2021
DOI: 10.1002/uog.23658
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous fetoscopic spina bifida repair: effect on ambulation and need for postnatal cerebrospinal fluid diversion and bladder catheterization

Abstract: Objective A trial comparing prenatal with postnatal open spina bifida (OSB) repair established that prenatal surgery was associated with better postnatal outcome. However, in the trial, fetal surgery was carried out through hysterotomy. Minimally invasive approaches are being developed to mitigate the risks of open maternal–fetal surgery. The objective of this study was to investigate the impact of a novel neurosurgical technique for percutaneous fetoscopic repair of fetal OSB, the skin‐over‐biocellulose for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 34 publications
5
24
1
2
Order By: Relevance
“…Lapa et al tested the patch in fetal rabbit and sheep models before applying it clinically for fetoscopic SBA surgery. 16,22,[44][45][46] In her initial study in the rabbit model, the repaired defect healed completely, with the patch remaining in place, and "without any signs of tissue rejection" at term. 22 We documented similar effects with both Duragen and Durepair in the same model she used.…”
Section: Discussionmentioning
confidence: 99%
“…Lapa et al tested the patch in fetal rabbit and sheep models before applying it clinically for fetoscopic SBA surgery. 16,22,[44][45][46] In her initial study in the rabbit model, the repaired defect healed completely, with the patch remaining in place, and "without any signs of tissue rejection" at term. 22 We documented similar effects with both Duragen and Durepair in the same model she used.…”
Section: Discussionmentioning
confidence: 99%
“…An ethical discussion regarding fetal surgery in twins discordant for diaphragmatic hernia concluded that certain maternal–fetal surgical interventions may be ethically permissible if the risk to the unaffected twin is minimal and the procedure improves the likelihood of survival of the compromised fetus 17 . Although OSB is not lethal, the benefits of prenatal surgery are established 1,2,8,20,21 . We believe the risk to the unaffected twin may be minimized by delaying surgery to 28–30 gestational weeks to mitigate the risk of extremely preterm birth in case delivery is required during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…102,119,154 Short-term neurologic outcomes by 12 months of life were similar: 43.8% of patients undergoing fetoscopic repair required a ventriculoperitoneal shunt insertion or other CSF diversion procedure compared with 40.8% of patients in the original MOMS trial. 102,119 Recently, several collaborating centers published long-term neurologic outcomes at 30 months of life, demonstrating a 46-54% independent ambulation rate in patients undergoing prenatal fetoscopic repair 156,157 compared with the 42% independent ambulation rate at 30 months of life observed in the original MOMS trial. 102 In addition, 61% of patients undergoing fetoscopic repair demonstrated independent voiding without clean intermittent catheter use at 30 months of life 156 compared with 38% of patients after open prenatal repair at the long-term follow-up (mean age 7.4 years).…”
Section: The Percutaneous Fetoscopic Technique Is Per-mentioning
confidence: 99%